The Influence Of The Big Five Personality And Readiness To Change On Civil Servants Performance With Job Satisfaction As An Intervening Variable In Penajam Paser Utara Regency - Aryanti, Inanta Nofi; Rahmawati, Rahmawati; Rahardjo , Djoko (SEAN Institute, 2024)
The bureaucratic simplification policy raises many pros and cons for Civil Servants. The personality and readiness of Civil Servants to change from each functional official as a result of simplification is important. It is feared that the feeling of insecurity that arises due to unpreparedness for change will influence behavior in the organization which could later disrupt performance. Job satisfaction is also something worth paying attention to because several studies have shown that there is a relationship with the quality of employee performance. This research uses a descriptive method with a quantitative approach. Population of 230 Civil Servants in PPU regency with a sample of 92 Civil Servants using the Slovin formula. The results of the research show that Personality on Satisfaction has a positive and significant direct influence, Readiness to Change on Satisfaction has a positive and significant direct influence, Personality on Performance has a positive and significant direct influence, Readiness for Change on Performance has a positive and significant direct influence , Satisfaction with Performance has a positive and significant direct influence, Satisfaction mediates the influence of Personality on employee Performance indirectly, Satisfaction mediates the influence of Readiness to Change on employee Performance.